(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
One of the recent and most momentous developments in the field of media and communication is that of mobile applications (also called as app). These are software which may be installed on small, wireless computing devices such as smart phones and tablets. This technology has transformed the role of phone from a communication device to a complete package loaded with a range of productive tools for information, entertainment, banking, education, online bookings.